Equity research: novo nordisk - Carati, Alessandro (2021)
The aim of the thesis is that to asses show the future will unfold for the pharma company Novo Nordisk taking into account the entry of a disruptive and innovative competitor: Virta Health. As we will later further develop, Novo Nordisk has a strong pipeline of products, with its main focus on Diabetes. As we will later further develop, Novo Nordisk has a strong pipeline of products, with its main focus on Diabetes. Market potential for diabetes lies mainly in diabetes Type 2 which accounts for 90% to 95% of diabetes cases. Virt a strictly targets Type 2 diabetes, setting itself apart by reversing the disease or preventing it on a whole, without the use of medicines but through a dietary solution. Let me take you on this journey: together we will discover the secrets of diabetes and the pharma industry. Thanks to scientific innovation and research, new solutions and cures are being discovered as you read.